DEVELOPMENT OF PAYMENT GATEWAY DIGITALIZATION USING MIDTRANS IN THE USE OF HALODOC - Hasibuan, Siti Hawa; Nasution, Muhammad Irwan Padli; Sundari, Sri Suci Ayu (Transpublika Publisher, 2023)
The digital age improves old technology to make life easier. Users and providers benefit from new technologies. New technology gives service providers and users significant opportunities. Online health applications, used by businesses to grow, can improve the health system and user experience. To compete with other online health care providers, a company must assess the app's usability and satisfaction. In this study, the author's intent and purpose is to try to describe how much influence service quality has in the development of digitization using midtrans in the use of the halodoc application. The results show that there is a strong influence between the current information technology developments. meaning here it can be seen that the more advanced the development of technology in the digital era, the more living things need communication tools to get information, because it has become an important requirement in order to be able to interact and communicate properly. After conducting research using several methods, the conclusions obtained are the need for instant applications that help find drugs and the location of the nearest pharmacy, reduce the number of queues and make it easier for users in terms of payments.